Pneumocephalus and Suppurative Meningoencephalitis in a Dog after Craniofacial Trauma - Yamaguchi, Larissa Sasaki; Gazzone, Alexandre Coultro; Caramalac, Silvana Marques; Caramalac, Simone Marques; Geller, Felipe Foletto; Palumbo, Mariana Isa Poci (Acta Scientiae Veterinariae, 2022)
Background: Pneumocephalus is characterized by the presence of gas in the intracranial compartment, and it can develop because of trauma or craniofacial surgery or spontaneously. Clinical signs start within days or months after the injury and vary according to the site of involvement. Computed tomography is the ideal diagnostic tool, however skull radiography can also be used. Treatment varies according to the severity of the case, and it can be conservative or associated with surgical intervention in the most severe cases. The purpose of this report is to describe the case of a dog that developed pneumocephalus and suppurative meningoencephalitis after head trauma caused by a bite from another dog. Case: A 2-month-old bitch, mixed breed, with 3.2 kg, was referred to the veterinary hospital because it had been bitten on the head by another dog. Shortly after the incident, the animal showed no clinical signs. However, 2 days later, the bitch became depressed and in persistent lateral decubitus. A lesion with a crust of approximately 0.5 cm was found close to the occipital region, with bone irregularity on palpation. The animal was in lateral decubitus with muscular hypotonia, bilateral mydriasis unresponsive to light and stupor. Radiographic images showed parietal fracture and pneumocephalus. Based on the findings of physical and laboratorial exams, diagnosis of suppurative meningoencephalitis and pneumocephalus secondary to craniofacial trauma was established. Empirical broad-spectrum antimicrobial therapy was started in addition to mannitol, corticoids, and analgesics. The animal was referred for surgical debridement by trepanation, when samples were collected to bacterial culture, which was negative. Despites the care, the animal died 14 h after the surgical procedure. Histopathological examination of the frontal cortex was performed, being the histological changes compatible with suppurative meningoencephalitis. Discussion: Dog bites on the head and neck are particularly severe, and can create intracranial bleeding, disfigurement of the face, damage to peripheral structures or cranial fractures. In this report, through radiographic images, it was found that the patient had an intracerebral aerocele, since there was presence of gas in the intracranial compartment. This alteration should always be considered in animals with neurological alterations and a history of craniofacial trauma. The main neurological changes observed in the reported case were unresponsive to mydriasis and altered mental status 2 days after the trauma, and this delay in the onset of clinical signs is frequently reported in cases of pneumocephalus. Neutrophilia and leukocytosis observed can be justified by the suppurative meningoencephalitis, confirmed by the histopathological exam. Antimicrobial therapy should be started as soon as possible, and the choice must be based on their capacity to cross the blood-brain barrier and the broad spectrum. The administration of antibiotics before collecting the material for bacterial culture may explain the negative result of this test, so that it is not possible to determine whether the intracranial gas observed on the radiograph may have developed from the trauma or because of gas-producing bacteria. Head trauma can induce suppurative meningoencephalitis and pneumocephalus even in the absence of perforating wounds at the time of the consultation. The neurological signs can start days after the trauma. Besides the clinical and surgical treatments, the prognosis of any bacterial infection of the central nervous system is poor. Keywords: aerocele, brain syndrome, Glasgow scale, radiography, trepanation.